THE EFFECT OF INVESTMENT OPPORTUNITY SET and SIZE OF THE COMPANY AS TOWARD CASH DIVIDEND POLICY (Empirical Study of LQ45 Companies Listed on the Indonesia Stock Exchange in 2020-2021 - Indah Zakiyah (PROGRAM STUDI AKUNTANSI - UNIVERSITAS MUHAMMADIYAH KUPANG, 2022)
The background of this research is the limited data for investors when determining the investment portfolio in stocks. The data show that not all companies listed on the Indonesia Stock Exchange distribute dividends. There is also data that net income after tax is not the only consideration for companies to distribute dividends. This study aims to analyze the effect of IOS and company size on cash dividend policy in LQ45 companies in 2020-2021. The problems in this study are (1). Does IOS affect the cash dividend policy? (2). Does Company Size affect the cash dividend policy? (3). Whether IOS and Company Size affect together on Cash dividend policy? The analytical method used is descriptive analysis and inferential analysis using SPSS Method. The data used are secondary data in the form of 2020-2021 financial statements from www.idx.co.id. The results of the analysis showed that IOS T count 3.751 >T table 0.678283 there is effect of the IOS variable on the cash dividend policy variable. SIZE T count 2.590 > T table 0.678283 there is effect of the SIZE variable on the cash dividend policy variable. And last, because F Count = 0.989 < F Table = 3.132, there is no simultaneous effect of the IOS and SIZE variables on the cash dividend policy